2018
DOI: 10.1007/s00128-018-2376-7
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Concentrations in European Pond Turtles (Emys orbicularis) from Brenne Natural Park, France

Abstract: We assessed trace elements concentration in European pond turtle (Emys orbicularis) from Brenne Natural Park (France). We sampled road-killed turtles (N = 46) to measure the concentrations of 4 non-essential (Ag, Cd, Hg, and Pb) and 10 essential (As, Co, Cr, Cu, Fe, Mn, Ni, Se, V, and Zn) elements in muscle, skin, liver and claws. Body size or sex did not influence the concentrations of most elements; except for Hg (liver, skin and claws) and Zn (muscle) which increased with body size. We found relatively high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
5
1
Order By: Relevance
“…The usefulness of freshwater turtles as bioindicators of Hg contamination has already been demonstrated in this species (Guillot et al 2018) and others (Bergeron et al 2007;Burger et al, 2009;Schneider et al 2009;Schneider et al 2010;Turnquist et al 2011;Hopkins et al 2013b;Slimani et al 2018). Consistent with these studies, our investigations also indicate that analysis of the claws of E. orbicularis is a useful noninvasive technique to monitor Hg contamination in a large number of individuals.…”
Section: Individual Determinants Of Hg Concentrationssupporting
confidence: 89%
See 4 more Smart Citations
“…The usefulness of freshwater turtles as bioindicators of Hg contamination has already been demonstrated in this species (Guillot et al 2018) and others (Bergeron et al 2007;Burger et al, 2009;Schneider et al 2009;Schneider et al 2010;Turnquist et al 2011;Hopkins et al 2013b;Slimani et al 2018). Consistent with these studies, our investigations also indicate that analysis of the claws of E. orbicularis is a useful noninvasive technique to monitor Hg contamination in a large number of individuals.…”
Section: Individual Determinants Of Hg Concentrationssupporting
confidence: 89%
“…Consistent with these studies, our investigations also indicate that analysis of the claws of E. orbicularis is a useful noninvasive technique to monitor Hg contamination in a large number of individuals. We found that juvenile individuals had lower Hg concentrations in their claws than older adult turtles indicating that Hg bioaccumulates during the life of E. orbicularis (Guillot et al 2018). Despite this difference between age classes (juveniles versus adults), we did not find any relationship between turtle size and Hg concentration, while such correlation has been previously recorded (Guillot et al 2018;Hopkins et al, 2013a).…”
Section: Individual Determinants Of Hg Concentrationscontrasting
confidence: 70%
See 3 more Smart Citations